2011
DOI: 10.1007/s12283-011-0063-6
|View full text |Cite
|
Sign up to set email alerts
|

Original characteristics of a new cycle ergometer

Abstract: The aim of this study was to describe and validate a new cycling ergometer with original characteristics that allow the measurement of biomechanical variables with position and crank inertial load used by the cyclist in field condition. The braking pedalling force, that permitted the simulation of the resistance to the cyclist in the field, is performed with a brushless electric motor. The validity and the reproducibility of the power output measurements were compared with the widely accepted SRM powermeter. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…It recruits a relatively large amount of muscle around the lower limbs and can elicit a large magnitude of power output 11 30 . Validity and reproducibility of cycle ergometers have also been confirmed in previous studies 4 6 23 24 29 . Other methods have also been developed to duplicate specific conditions of each sport and approximate muscles that are involved 8 22 25 26 27 , including an arm-cranking ergometer 7 and a rowing ergometer 5 13 17 19 30 .…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…It recruits a relatively large amount of muscle around the lower limbs and can elicit a large magnitude of power output 11 30 . Validity and reproducibility of cycle ergometers have also been confirmed in previous studies 4 6 23 24 29 . Other methods have also been developed to duplicate specific conditions of each sport and approximate muscles that are involved 8 22 25 26 27 , including an arm-cranking ergometer 7 and a rowing ergometer 5 13 17 19 30 .…”
Section: Introductionsupporting
confidence: 72%
“…The most elaborate component of our ergometer is the loading system (Apowatec, Apowatec Corporation, Yashio, Japan). Existing ergometers include various loading devices 6 , such as the ECB (PowerMax V3 Series, Combi Wellness Corporation, Tokyo, Japan), and friction-based loading (Monark Series, Monark Exercise AB, Vansbro, Sweden). In our study, the ECB was adopted because it has an advantage in strictness and easiness of load adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the study [ 7 ] did not allow for a familiarisation period to the selected exercise protocol (Windgate Anaerobic Test) [ 27 ] and subjects are prone to fatigue while performing repeated bouts of the Windgate Anaerobic Test thus affecting the reproducibility and reliability of the results [ 28 , 29 ]. Crucially, the ergometer (Cyclus 2) used in the study [ 7 ] has not been shown to be a valid or reliable tool for measurement of power production [ 30 , 31 ]. It is possible that these factors may confound the results of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the importance of recording power with an appropriate level of accuracy and reliability for the power meters' intended use, a number of studies have been conducted to establish the level of accuracy and reliability of commercially available cycling power meters such as the SRM (Jones & Passfield, 1998;Lawton, Martin & Lee, 1999;Gardner et al, 2004, Abbis et al, 2009, PowerTap® (Gardner et al, 2004;Bertucci, Duc, Villerius, Pernin, & Grappe, 2005), Ergomo Pro (Duc et al, 2007;Kirkland, Coleman, Wiles, & Hopker, 2008), Look Keo (Sparks, Dove, Bridge, Midgely, 2014), Polar® S710 (Millet, Tronche, Fuster, Bentley, & Candau, 2003), G-Cog (Bertucci, Crequy, & Chiementin, 2013), and power measuring cycle ergometers such as the Kingcyle (Balmer, Davison, Coleman, & Bird, 2000), Axiom Powertrain , Velotron (Abbis, Quod, Levin, Martin, & Laursen, 2009), Wattbike (Hopker et al, 2010) and a new design of ergometer (Bertucci, Grappe, & Crequy, 2011).…”
Section: Introductionmentioning
confidence: 99%